MANAJEMEN RETRIBUSI PARKIR OLEH DINAS PERHUBUNGAN KOTA PEKANBARU - Rahman, Auldia; ", Mayarni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The parking levy management in Pekanbaru city being held for regulate parking area and to increase local revenue Pekanbaru city. However, in it’s implementation still have a discrepancy with the valid provision and the attainment of total parking levy still far from the target. As a goverment institution that manages the parking levy in Pekanbaru city, Departement of Transportation of Pekanbaru be liable for manage parking levy and support to increase local revenue. The purpose of research is to find out how the parking levy management being manage by Departement of Transportation of Pekanbaru City. In the theory of George R. Terry, there are four functions of management i.e. planning, organizing, directioning, and observating. The research used descriptive qualitative method with the purposive sampling technique. Informants in this study are the Departement of Transportation Pekanbaru City, Parking Coordinator officer, Parking officer, and the users of parking area. The results of research of qualitative descriptive analysis can be concluded, Parking Levy Management by Departement of Transportation Pekanbaru Cityn did not function maximally because there are still unit of work that did not carry out theirs duties and authority appropriate provisions and did not achieve the target of parking levy. Factors that affect the parking levy management in Pekanbaru city was consciousness factor, time factor, and service factor. Keyword : Management, Parking Levy